2015
DOI: 10.1002/ccd.25945
|View full text |Cite
|
Sign up to set email alerts
|

Clinical predictors of mortality following rotational atherectomy and stent implantation in high‐risk patients: A single center experience

Abstract: ObjectivesOur aim was to assess the procedural success and determine the clinical predictors of postprocedure mortality, following rotational atherectomy (RA) and stenting in high‐risk patients.BackgroundRA is mainly used to facilitate stenting in complex lesions. Outcomes involving RA and stenting have been investigated, yet high‐risk patients have not been adequately described.MethodsData of 218 consecutive patients who underwent RA were evaluated in a prospective register. Primary endpoints were the angiogr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
33
1
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 15 publications
1
33
1
1
Order By: Relevance
“…Several authors have reported that RA followed by stent implantation is a feasible method in terms of high rate of procedural success and favorable long-term outcomes in heavily calcified coronary lesions. [2][3][4][5][6] It is difficult to recognize underexpansion of the balloon and adequate lesion preparation before stenting. IVUS before stenting can help to avoid underexpansion of the stent without sufficient lesion preparation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several authors have reported that RA followed by stent implantation is a feasible method in terms of high rate of procedural success and favorable long-term outcomes in heavily calcified coronary lesions. [2][3][4][5][6] It is difficult to recognize underexpansion of the balloon and adequate lesion preparation before stenting. IVUS before stenting can help to avoid underexpansion of the stent without sufficient lesion preparation.…”
Section: Discussionmentioning
confidence: 99%
“…1) If there is a calcified lesion with insufficient expansion after ballooning with non-compliant balloons, rotational atherectomy (RA) is one of the available options for pretreatment of calcified plaques. [2][3][4][5][6] RA might also be used to remove an underexpanded stent. However, there are several problems associated with RA for removal of underexpanded stents.…”
mentioning
confidence: 99%
“…The two affirmed as most effective in facilitating PCI in HCCL are (RA and recently introduced orbital atherectomy (OA). RA showed favourable results in treating HCCL in recent registries; however, there are no randomised trials concerning the use of RA in patients with severe TLC and AMI [20][21][22]. OA, a newcomer to coronary interventions, was first introduced in coronary arteries in 2013 in the ORBIT I trial [23].…”
Section: Discussionmentioning
confidence: 99%
“…This is in concordance with our experience, as only one patient included in the study underwent RA. Despite good results of patients with ACS treated with RA, this plaque modification technique is not applicable to all ACS patients, so we should strive for new solutions to improve the outcomes of all patients with ACS and severe TLC [20].…”
Section: Discussionmentioning
confidence: 99%
“…In support of the more frequent application of rotational atherectomy in high risk, no option patients, an article in this issue of CCI by Edes et al [2] describes the outcome after rotational atherectomy in a high-risk population [left main coronary artery (LM) in 20.2%, left ventricular ejection fraction (LVEF) < 50% in 37.6] of elderly patients (mean age 70 years) with complex, often heavily calcified lesions (83.1%) over half of which were unable to be opened by traditional methods. Despite the overall illness of the population, the procedure and in-hospital major adverse cardiac events (MACE) was amazingly low at 2.3%.…”
mentioning
confidence: 95%